Effect of early versus delayed activation of thoracic epidural anesthesia on plasma pro-atrial natriuretic peptide to indicate deviations in central blood volume during esophagectomy. Issue 8 (24th May 2019) - Strandby, Rune B; Ambrus, Rikard; Achiam, Michael P; Goetze, Jens P; Secher, Niels H; Svendsen, Lars B
Abstract : Background and Objectives: A side effect to thoracic epidural anesthesia (TEA) is hypotension induced by central hypovolemia. This study addressed whether early activation (EA) versus late activation (LA) of TEA affects plasma pro-atrial natriuretic peptide (proANP) reflecting deviations in the central blood volume (CBV). We hypothesized that EA TEA would reduce plasma proANP, thus reflecting a decrease in CBV. Methods: A randomized, controlled, single-blinded trial was conducted. Patients undergoing open esophagectomy were randomized to EA (n=25, after induction of general anesthesia) or LA TEA (n=25, after re-established gastric continuity) with the epidural catheter placed at the interspaces Th7-8 or Th8-9. Plasma proANP was determined repetitively along with hemodynamic variables and administration of fluid/vasopressors as postoperative complications were noted. Results: With EA TEA, plasma proANP decreased following induction of anesthesia to the end of surgery (13%; 113±68 to 99±49 pmol/L; p=0.026), but that was not the case in the LA group (3%; 97±44 to 94±49 pmol/L; p=0.565) despite equal fluid balance (+1584±582 vs +1560±563 mL; p=0.888). Accordingly, the EA group required excessive treatment with vasopressors to maintain MAP >60 mm Hg during surgery (2.7±2 vs 1.6±1.4 ephedrine boluses; p=0.033 and infusion of phenylephrine for 216±86 vs 58±91 min; p<0.001). Plasma proANP and fluid balance were correlated only for EA patients (r=0.44; 95% CI 0.04 to 0.91; p=0.033). Conclusions: EA TEA reduces plasma proANP indicating that CBV becomes affected. Based on a correlation between plasma proANP and fluid balance, a 2000 mL volume surplus of lactated Ringer's solution is required to maintain plasma proANP stable during open esophagectomy. Trial registration number: 2014-002036-14 (https://www.clinicaltrialsregister.eu/ctr-search/search?query=2014-002036-14 ).